2012
DOI: 10.1002/eco.1256
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term air temperature changes in a Central European sedge‐grass marsh

Abstract: In this study, we have analysed the series of daily air temperatures from 1977 to 2009 measured in a sedge‐grass marsh ecosystem near the town of Třeboň, Czech Republic (Central Europe). Annual averages of daily mean, minimum and maximum temperatures were analysed. Possible significant increases were recorded for all these values during the study period. The annual average of daily maximum temperatures increased on average by 0.0827 °C per year. The annual average of daily mean air temperatures increased by 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
(34 reference statements)
0
1
2
Order By: Relevance
“…Moreover, we expect changes in the geographical position of this line to affect the continental availability of wetlands to wintering waterbirds. At the present time, long-term January temperatures do not show any significant trends in the study area, in contrast to the observed trend for increasing monthly temperatures in the period from April up to and including August (Dušek et al 2012). Similarly, we assume a higher importance to sufficient running water and sites with a higher proportion of urban areas and other wetlands in their surroundings, which we consider as variables that reduce the effect of winter harshness.…”
Section: Introductioncontrasting
confidence: 68%
See 1 more Smart Citation
“…Moreover, we expect changes in the geographical position of this line to affect the continental availability of wetlands to wintering waterbirds. At the present time, long-term January temperatures do not show any significant trends in the study area, in contrast to the observed trend for increasing monthly temperatures in the period from April up to and including August (Dušek et al 2012). Similarly, we assume a higher importance to sufficient running water and sites with a higher proportion of urban areas and other wetlands in their surroundings, which we consider as variables that reduce the effect of winter harshness.…”
Section: Introductioncontrasting
confidence: 68%
“…Central European wetlands would seem to offer less suitable conditions for wintering waterbirds, but, to the contrary, the importance of these sites have been increasing over the last decades (Keller 2011;Fox et al 2010;Musil et al 2011;Slabeyová et al 2014), no doubt due to the changing environment generating variation in critical factors, such as weather (Goss-Custard et al 1994;Sutherland 1998). However, significant changes in winter temperatures are more apparent in some other parts of the same wintering flyway, as exemplified by the increasing numbers in Finland , Pavón-Jordán et al 2015, whereas in our study area the long-term January temperatures seem to be remaining stable (Musilová et al 2009;Dušek et al 2012). Many species can be expected to survive climate change as long as they are able to colonize new regions (Thomas et al 2012).…”
Section: Resultscontrasting
confidence: 48%
“…The sedge-grass marsh (location of the meteorological station is 49°01′ 29" N, 14°46′13" E) is a flat area at an altitude of 426.5 m above sea level. The mean annual air temperature and mean annual precipitation, for a 35-year period between 1977 and 2011, were 7.6 °C and 614 mm, respectively (Dusek et al, 2012b). For previous ecological studies that focused on the "Wet Meadows" sedge-grass marsh site see Jenik and Kvet (1983) and Kvet et al (Holubickova, 1959;Gazda, 1983;Prach, 1993;Prach and Soukupova, 2002;Prach, 2008).…”
Section: Site Descriptionmentioning
confidence: 96%